Diagnosis of COVID-19 disease based on a modified convolutional neural network on the example of lung X-rays - Jamil Alsayaydeh, Jamil Abedalrahim; Fedorchenko, Ievgen; Oliinyk, Andrii O.; Stepanenko, Aleksandr; Fedoronchak, Tetiana; Korniienko, Serhii; Chornobuk, Maksym (Asian Research Publishing Network (ARPN), 2023)
As a result of the study, a machine learning model based on a modified convolutional neural network was developed to diagnose COVID-19 lesions from lung X-rays. Due to the improvement of the network architecture, it was possible to obtain a classification accuracy of 91%. The developed model can be used in the field of health care to assist medical staff in the analysis of X-rays, which will reduce the likelihood of medical error.